THE EFFECT OF DESTINATION IMAGE AND TOURIST EXPERIENCE ON PURCHASING INTENTION TO TIDUNG ISLAND, DKI JAKARTA, DURING THE COVID-19 PANDEMIC - Tri Djoko Sulistio; Jason Augustian; Rina Fitriana; Nurul Ma’rifah (Jurnal Scientia, 2023)
The purpose of this study is to find out how the influence of Sales Promotion and Consumer Trust on Interest in Staying at a four-star hotel in Jakarta during the COVID-19 pandemic. The research method used is descriptive quantitative research method. The study used a sample of 100 respondents with 16 statements. Sales Promotion with a mean of 3.50 in the very good category, Consumer Trust with a mean of 3.52 in the very good category, and Interest in Staying with a mean of 3.36 in the very high category. Sales Promotion has an effect on interest in staying by 16% and the remaining 84% is influenced by other variables not examined in this study. Consumer Trust has an effect on interest in staying by 43.5% and the remaining 56.5% is influenced by other variables not examined in this study. Sales Promotion and Consumer Trust have an effect on Interest in Staying by 45.1% and the remaining 54.9% is influenced by other variables not examined in this study. The contribution of this research is to inform the hotel management about the use of Traveloka application during pandemic and to provide recommendations to increase consumers’ trust so that consumer interest in staying increases